Predictors of fear of childbirth and normal vaginal birth among Iranian postpartum women: a cross-sectional study - Mortazavi, Forough (BMC Pregnancy Childbirth, 2021)
BACKGROUND: Fear of childbirth (FOC) may contribute to postpartum depression, impaired maternal-infant relation, and preference for cesarean in future pregnancies. We aimed to investigate predictors of FOC and normal vaginal birth among postpartum women who had planned for a normal vaginal birth. METHODS: This cross-sectional study was conducted in 2019 with postpartum women during the first 24 h after the birth. A sample of 662 women, selected using a convenient sampling method, filled out the questionnaire composed of socio-demographic and obstetric questions and the Wijma Delivery-Expectancy Questionnaire (W-DEQ). We used multiple logistic regression analyses to determine predictors of FOC and normal vaginal birth. RESULTS: The percentage of women with mild (score ≤ 37), moderate (38–65), high (66–84), severe (85–99), and intense FOC (score ≥ 100) were 7.9, 19.5, 40.9, 21.1, and 10.6% respectively. Predictors of intense FOC were age < 30, primiparity, low maternal satisfaction with pregnancy, and a low level of perceived marital satisfaction. Overall, 21.8% of women gave birth by cesarean. Predictors of normal vaginal birth were birth weight < 4 kg, spontaneous onset of labor pain, mother’s age < 30, term pregnancy, having a doula, multiparity, satisfaction with husband’s support, and overall satisfaction with pregnancy. A high level of perceived marital/sexual satisfaction was a risk factor for cesarean. Mode of birth was not a predictor of postpartum FOC. CONCLUSIONS: The rate of severe and intense FOC among this group of postpartum women is high. Our findings highlight modifiable factors for reducing FOC and increasing normal vaginal birth. In designing programs to increase the rate of normal vaginal birth, the following factors should be considered: limiting induced labor, encouraging women to recruit a doula to help them at labor, facilitate husband’s attendance throughout antenatal/intrapartum, and postnatal care to support his wife, and pay attention to women’s common misunderstandings about the effect of vaginal birth on marital/sexual relationship. Our findings indicate that seeking novel ways to promote marital/sexual satisfaction and helping women to have a smooth, hassle-free pregnancy may contribute to a reduction in the rate of the FOC. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12884-021-03790-w.